Non-linear orthotropic numerical simulation for monitoring wood embedment tests according to BS EN 383 (2007) Standard European - Junior, Amauri da Silva Ribas [UNESP]; Criado, Tayla Castilho; Souza, Alexandre Jorge Duarte de [UNESP]; Molina, Julio Cesar (FapUNIFESP (SciELO), 2024)
Most studies conducted in Brazil to analyze the behavior of connections for wooden structures have an experimental nature, and few studies consider numerical analyses based on the Finite Element Method (FEM). In embedment tests, understanding stress concentration points is crucial for identifying primary failure modes and determining the experimental strength values. The objective of this study was to present a numerical modeling strategy to monitor the behavior of test specimens in embedment tests according to BS EN 383: 2007 [1]. The ANSYS [2] software was employed for numerical modeling, considering various strength criteria for the involved materials. The models incorporated elastic and plastic properties of the materials obtained through laboratory experimental characterization. Experimental embedment tests were conducted on specimens in parallel and perpendicular directions to the fibers, using 6.72 mm diameter metal pins for numerical result calibration. The proposed numerical modeling strategy allowed for the global analysis of embedment test specimens and the examination of localized aspects of interest, such as stress concentrations, a factor challenging to quantify in experimental analyses.
Simulação numérica ortotrópica não linear para monitoramento de ensaios de embutimento de madeira de acordo com a norma europeia BS EN 383 (2007)
Keywords: ANSYS; embedment; numerical simulation; stresses; wood